Separating invariants for arbitrary linear actions of the additive group - Dufresne, Emilie; Elmer, Jonathan; Sezer, Müfit (Springer, 2014)
We consider an arbitrary representation of the additive group Ga over a field of characteristic zero and give an explicit description of a finite separating set in the corresponding ring of invariants.